(untitled) (Journal of Oriental Studies, 2018)
The article considers the place and significance of the Chinese language in China’s foreign policy. An assessment is made of how much China is paying attention to its language, as the main component of the “soft power” policy. The formation of the international language policy of China, its basic forms and directions is considered